1999
DOI: 10.1002/(sici)1097-0010(199906)79:8<1099::aid-jsfa332>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and degradation of adenosine triphosphate in cod ( Gadus morhua ) at subzero temperatures

Abstract: This study has demonstrated that the extraction step is very important when analysing ATP and its degradation products. An important factor is whether the sample is fresh, frozen or thawed when homogenised since thawing of the sample will lead to rapid loss of ATP. During frozen storage it was found that ATP in cod (Gadus morhua) was stable at −40 °C in small samples for at least 12 weeks. At −20 °C it was found that ATP content increases initially and thereafter falls. It was demonstrated that degradation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…The reservoirs of ATP and glycogen have probably been depleted during the frozen storage and/or the thawing prior to salting. Energy may have been dissipated as heat rather than used as mechanical energy, and hence unavailable for contractions at thawing (Cappeln et al, 1999;Cappeln & Jessen, 2001) and salting. Recent investigations have shown that fresh pre-rigor salmon fillets contracted 14% in length during rigor, whereas fillets frozen pre-rigor did not develop thaw rigor muscle contraction (Einen et al, 2002).…”
Section: Mass Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…The reservoirs of ATP and glycogen have probably been depleted during the frozen storage and/or the thawing prior to salting. Energy may have been dissipated as heat rather than used as mechanical energy, and hence unavailable for contractions at thawing (Cappeln et al, 1999;Cappeln & Jessen, 2001) and salting. Recent investigations have shown that fresh pre-rigor salmon fillets contracted 14% in length during rigor, whereas fillets frozen pre-rigor did not develop thaw rigor muscle contraction (Einen et al, 2002).…”
Section: Mass Transfermentioning
confidence: 99%
“…The maximum breakdown of high energy phosphorous compounds in frozen cod muscle has been found to occur, around -3/-2°C (Nowlan & Dyer, 1974;Cappeln, Nielsen & Jessen, 1999). Prolonged thawing around -3/-2°C is, therefore, favourable to avoid thaw-rigor in cod.…”
Section: Introductionmentioning
confidence: 97%
“…The freezing of fish is an effective way of long term preservation and it has been shown that fish stored for up to three months under ideal conditions cannot be distinguished from fresh fish regarding color, taste and texture (Cappeln et al, 1999;Nielsen and Jessen, 2007).Freezing and frozen storage of fish muscle may, however, lead to denaturation and aggregation of especially myofibrillar proteins. These changes result in altered functional properties, changed textural attributes and reduced water holding capacity and juiciness.…”
Section: Introductionmentioning
confidence: 99%
“…Fresh fish products are often regarded as superior to preserved products, but if fish is frozen immediately after catch and processing, stored at low, non-fluctuating temperatures, and thawed in the best way according to its rigor-state, the quality can be as good or better than fresh fish stored for several days at 0 • C (Cappeln et al, 1999;Nielsen and Jessen, 2007). Factors that affect the quality of fish during frozen storage are quality of the initial raw material, storage conditions before freezing (e.g., time on ice), freezing rate, frozen storage temperature and time, temperature fluctuations, thawing procedure, and prevention against oxidation (light and oxygen).…”
Section: Introductionmentioning
confidence: 99%
“…Factors that affect the quality of fish during frozen storage are quality of the initial raw material, storage conditions before freezing (e.g., time on ice), freezing rate, frozen storage temperature and time, temperature fluctuations, thawing procedure, and prevention against oxidation (light and oxygen). Quality deteriorating processes can occur at all points of fish processing, and the most common are physical alterations in the texture caused by large ice crystals (protein denaturation), freezer burn, lipid oxidation, protein oxidation, and discolorations (Sikorski et al, 1976;Sikorski, 1978;Cappeln et al, 1999;Careche et al, 1999;Herrera et al, 2001;Leelapongwattana et al, 2005). Numerous studies have focused on quality related processes occurring in the temperature interval between 0 and −30 • C, and it is well known that storage at −20 • C or higher is insufficient in keeping a high quality.…”
Section: Introductionmentioning
confidence: 99%